Effects of soil particle size on rainfall-induced erosion of near-horizontal layered slopes - Chenxin Liu; Zizhao Zhang; Lilong Cheng; Yamei Wang; Xinyu Liu; Runsen Lai; Qianli Lyv (PLoS ONE, 2025)
The problem of soil erosion is prominent in the arid region of northwest China, and the Kapo in Wensu County, Xinjiang is highly susceptible to erosion and damage disasters due to the formation of chalky high steep slopes affected by rivers. In order to provide theoretical support for slope prevention and control, this paper investigates the erosion damage characteristics of three different grain size compositions of nearly horizontal laminated soil slopes under rainfall by using rainfall simulation equipment in an indoor model box test. The results show that rainfall, slope soil properties and cracks are the main causes of erosion damage on slopes. As rainfall increases, the slope shows regressive damage from the foot of the slope to the top of the slope. Soil slopes with coarse-grained sand have less erosion damage due to good permeability of the sand layer; slopes with fine soil particles have weak erosion resistance and severe gully erosion. The dominant seepage channels formed by cracks play a significant role in the erosion damage of slopes.